Processo de formação de educadores sociais na área da infância e juventude - Vangrelino, Ana Cristina dos Santos (Universidade Federal de São Carlos, 2004)
The present research investigates professionals of Human Sciences at the assistance of street children and adolescents. It was tried to identify and analyses their concepts of child, adolescent, education and educator built during their personal and professional life. To achieve this, three educators were interviewed at the Yellow House Project of the Social Assistance of Campinas, its purpose being the assistance of children and adolescents in hazardous conditions. The research was conducted to the formation processes of such educators prior to, after and during their involvement with that project. Thus the research offers subsidies to proposals of educator formation, in general, and for the education of children and adolescents in hazardous conditions in particular.
Keywords: Educação e formação de educadores de rua ou sociais; Crianças e adolescentes em risco social; Institucionalização; Práticas sociais e processos educativos; CIENCIAS HUMANAS::EDUCACAO